Genetic structure and demographic history of Cycas chenii (Cycadaceae), an endangered species with extremely small populations - Rui Yang; Xiuyan Feng; Xun Gong (Plant Diversity, 2017)
Geological activities and climate oscillations during the Quaternary period profoundly impacted the distribution of species in Southwest China. Some plant species may be harbored in refugia, such as the dry-hot valleys of Southwest China. Cycas chenii X. Gong & W. Zhou, a critically endangered cycad species, which grows under the canopy in subtropical evergreen broad-leaved forests along the upstream drainage area of the Red River, is endemic to this refugium. In this study, 60 individuals of C. chenii collected from six populations were analyzed by sequencing two chloroplast intergenic spacers (cpDNA: psbA-trnH and trnL-trnF) and two nuclear genes (PHYP and RBP-1). Results showed high genetic diversity at the species level, but low within-population genetic diversity and high interpopulation genetic differentiation. A Bayesian phylogenetic tree based on cpDNA showed that five chloroplast haplotypes were clustered into two clades, which corresponds to the division of the western and eastern bank of the Red River. These data indicate a possible role for the Red River as a geographic barrier to gene flow in C. chenii. Based on our findings, we propose appropriate in situ and ex situ conservation strategies for C. chenii.